Assessing the Existence of Corporate Shared Value in Companies Based on CSR Reports - Zemanová, Barbora; Pavelka, Ondřej (Univerzita Hradec Králové, 2023)
Rising customer demands, growing pressure from legislation, and the expectations of stakeholders motivate companies to adopt corporate social responsibility (CSR). For companies that want to build their reputation, remain competitive, and gain customer and employee loyalty, socially responsible behavioris essential. A successful company is one that focuses on making financial profits while also contributing, both in the form of concern for natural conditions and the welfare of the community. CSR activities do not necessarily coincide with the area in which the company does business. However, improvement activities can be approached systematically and purposefully based on the activities of the company. This is the case of creating corporate shared value (CSV). A gap in the literature for scientific research was found after the evaluation of earlier works. Indicators and a clear approach are still lacking to determine if the company is producing CSV or just CSR. The aim of this paper is to identify key indicators of CSV and to evaluate them through the CSR reports of companies. Ten multinational companies have been selected and examined. A benchmarking-scoring technique based on several defined qualitative and quantitative indicators was used for assessment to provide a view of compliance with CSV principles.
Hodnocení existence sdílené hodnoty ve firmách na základě zpráv o společenské odpovědnosti firem
Keywords: corporate shared value; CSV; corporate social responsibility; Global Reporting Initiative; CSR reports; sdílená hodnota podniku; CSV; společenská odpovědnost podniků; globální reportovací iniciativa; CSR reporty